Inhibition of PKR by Viruses - Cesaro, Teresa; Michiels, Thomas (Frontiers in Microbiology, 2021)
Cells respond to viral infections through sensors that detect non-self molecules, and through effectors, which can have direct antiviral activities or adapt cell physiology to limit viral infection and propagation. Eukaryotic translation initiation factor 2 alpha kinase 2 (EIF2AK2), better known as PKR, acts as both a sensor and an effector in the response to viral infections. After sensing double-stranded RNA molecules in infected cells, PKR self-activates and majorly exerts its antiviral function by blocking the translation machinery and inducing apoptosis. The antiviral potency of PKR is emphasized by the number of strategies developed by viruses to antagonize the PKR pathway. In this review, we present an update on the diversity of such strategies, which range from preventing double-stranded RNA recognition upstream from PKR activation, to activating eIF2B downstream from PKR targets.